Safety training need assessment for construction workers - Rahim, Mohamad Ariffin (2023)
The aim for this research is to determine the type and the needs of safety training need assessment for construction workers. It is hope that by providing safety training that is needed for construction forkers could minimize accident at site. In the context of this study, the population size is the construction companies at Bau Sarawak. There are 15 construction company in bau Sarawak. At this point, a detailed literature review was carried out in order to bolster and validate the research subject. Quantitative research techniques are developed in a way that helps disclose the perceptions of a target respondent in relation to a certain issue. The questionnaire was based on the Likert Scale, and it would make the respondents can make a choice for each question. collecting the information, the survey was conducted via the use of a Google Form. the information and data obtained during the previous stage will be compiled, and a summary based on the results of the study will also be created. From the results of the study that has been carried out, it has been determined that the type and the needs of safety training need assessment for construction workers and significance of determining whether or not they have met the necessary training requirements is rather high.